Streptomyces venezuelae ISP5230 Maintains Excretion of Jadomycin upon Disruption of the MFS Transporter JadL Located within the Natural Product Biosynthetic Gene Cluster - Forget, Stephanie M.; McVey, Jennifer; Vining, Leo C.; Jakeman, David L. (Frontiers in Microbiology, 2017)
JadL was identified as a Major Facilitator Superfamily (MFS) transporter (T.C. 2.A.1) through sequence homology. The protein is encoded by jadL, situated within the jadomycin biosynthetic gene cluster. JadL has, therefore, been assigned a putative role in host defence by exporting its probable substrates, the jadomycins, a family of secondary metabolites produced by Streptomyces venezuelae ISP5230. Herein, we evaluate this assumption through the construction and analysis of a jadL disrupted mutant, S. venezuelae VS678 (delta_jadL::aac(3)IV). Quantitative determination of jadomycin production with the jadL disrupted mutant did not to show a significant decrease in production in comparison to the wildtype strain , as determined by HPLC and by tandem mass spectrometry. These results suggest that efflux of jadomycin occurs upon disruption of jadL, or that jadL is not involved in jadomycin efflux. Potentially, other transporters within S. venezuelae ISP5230 may adopt this role upon inactivation of jadL to export jadomycins.